2020
DOI: 10.1109/access.2020.3030192
|View full text |Cite
|
Sign up to set email alerts
|

DDR-ESC: A Distributed and Data Reliability Model for Mobile Edge-Based Sensor-Cloud

Abstract: Cloud computing gained a lot of growth in the development of scientific and industrial domains due to its scalability, data analysis, portability, and storage abilities. The sensors and actuators facilitate wireless communication with real-time data gathering and local preprocessing. However, the huge amount of data collection and storage for such low powered nodes incurs the problem of reliability and efficient resource management. The technology of cloud computing provides an emerging paradigm for the sensor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Edge computing studies include those that focus on responsiveness [9], [18]- [21] and those that focus on reliability [22]. Responsiveness is enhanced by improving the caching algorithm of the objects in the data cache.…”
Section: Related Workmentioning
confidence: 99%
“…Edge computing studies include those that focus on responsiveness [9], [18]- [21] and those that focus on reliability [22]. Responsiveness is enhanced by improving the caching algorithm of the objects in the data cache.…”
Section: Related Workmentioning
confidence: 99%
“…A secure transmission on the cost of computation and routing overhead is a problem for 5G/6G. Data privacy in 5G/6G networks is driving a distributed and data reliability model for mobile edge-based sensor-cloud (DDR-ESC) [ 16 ]. In another work, the authors suggested using fuzzy logic for a network to protect mobile traveler’s information in IoT [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…A SERIOUS concentration has been made in the vehicular ad hoc network (VANET) technology [1], [2] since 1990s, and especially in the last decade, many advancements have been seen. Internet of Things (IoT) has been deployed (and being deployed) in various domains, such as agriculture [3], [4], healthcare [5]- [8], cloud computing [9], [10], edge computing [11], smart cities [12]- [14], smart homes [15], etc [16], [17]. However, VANETs in combination with IoT is a familiar research topic and has attracted attention from the research community at large [18].…”
Section: Introductionmentioning
confidence: 99%